The Insulinemic, Inflammatory, and Glycemic Potential of the Diet in Relation to Risk of Type 2 Diabetes. (29th May 2020) - Jin, Qi; Shi, Ni; Aroke, Desmond; Joseph, Joshua; Donneyong, Macarius; Adesanya, Timothy; Conwell, Darwin; Hart, Philip; Spees, Colleen; Clinton, Steven; Cruz-Monserrate, Zobeida; Brasky, Theodore; et al.
Abstract: Objectives: Dietary patterns that promote chronic systemic inflammation, hyperinsulinemia, or hyperglycemia may influence type 2 diabetes (T2D) risk. We evaluated an empirical dietary index for hyperinsulinemia (EDIH), empirical dietary inflammatory pattern (EDIP), glycemic index (GI), and glycemic load (GL), and risk of T2D among US postmenopausal women. EDIH and EDIP assess the insulinemic or inflammatory potential of habitual diets, irrespective of macronutrient content, and are based on plasma concentrations of insulin response or inflammatory biomarkers, respectively. The GI and GL assess postprandial glycemic potential based on carbohydrate content of the diet. Methods: We calculated dietary scores from baseline food frequency questionnaires among 73, 495 participants aged 50–79 years in the Women's Health Initiative Observational Study and Clinical Trials. We used multivariable-adjusted Cox regression to estimate hazard ratios (HR) and 95% confidence intervals (95% CI) for risk of T2D according to quintiles of dietary scores. Results: There were 11, 009 incident cases of T2D during a median 13.3 years of follow-up. In multivariable-adjusted analyses, participants in the highest dietary score quintiles (consuming the most hyperinsulinemic, proinflammatory, or hyperglycemic diets) were at highest risk of T2D compared to those in the lowest quintiles: EDIH: HR, 1.54(1.37, 1.74); Ptrend < .0001; EDIP: HR, 1.45 (1.29, 1.64); Ptrend < .0001). GI and GL were not associated with T2D risk: GI: HR, 0.99 (0.88, 1.12); Ptrend = 0.94; GL: HR, 0.98 (0.85, 1.12); Ptrend = 0.32. In subgroup analyses, associations of EDIH and EDIP with T2D risk were stronger among overweight or obese than normal-weight women (Pinteraction : EDIH = 0.02, EDIP = 0.003), and findings did not significantly vary by race/ethnicity. Conclusions: In this large sample of postmenopausal women, hyperinsulinemic, and pro-inflammatory dietary patterns were associated with higher risk of T2D, more so among overweight and obese women, whereas dietary glycemic potential was not associated with T2D risk. Funding Sources: NCI grant # R00CA207736 and the WHI program is funded by NHLBI grant #s HHSN268201600018C, HHSN268201600001C, HHSN268201600002C, HHSN268201600003C, and HHSN268201600004C.